An EST-SSR marker linked with yellow rust resistance in wheat - Ercan, S.; Ertugrul, F.; Aydin, Y.; Akfirat, F. S.; Hasancebi, S.; Akan, K.; Mert, Z. (Acad Sciences Czech Republic, Inst Experimental Botany, 2010)
Expressed sequenced tags containing simple sequence repeats (EST-SSRs) were used to identify molecular markers associated with yellow rust resistance in wheat (Triticum aestivum L.). A cross between yellow rust resistant (PI178383) and susceptible (Harmankaya99) wheat genotypes was performed and respective DNA pools from the resistant and susceptible F-2 seedlings were constructed. 78 EST-SSR primers were used for bulked segregant analysis and one EST-SSR marker (Pk54), identified as 200 bp fragment, was present in the resistant parent and resistant F-2 hybrids but not in the susceptible ones. 108 wheat genotypes differing in yellow rust resistance were screened with Pk54 and 68 % of the wheat genotypes, known to be yellow rust resistant, had the Pk54 marker, further suggesting that the presence of this marker correlates with yellow rust resistance.
Keywords: breeding; Puccinia striiformis f. sp tritici; Triticum aestivum